BILATERAL EPISIOTOMY FOR SUCCESSFUL PER VAGINAL DELIVERY OF TERATOLOGICAL TWIN FETUSES IN A DOE WITH VULVAL STENOSIS - S. Radhika; M. Srinivas; B. Chandra Prasad; N. Nagarjuna (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A full-term pregnant doe was presented with a history of dystocia. Ultrasonographic examination revealed the presence of two dead fetuses. On obstetrical examination, vulval stenosis was confirmed. Bilateral episiotomy was performed and twin dead fetuses were delivered per-vaginum by traction. Among the dead male twins, the first fetus had only prognathism second one had prognathism and a severe degree of congenital lordosis. Post-operative treatment was followed resulting in an uneventful recovery of the doe.